Antioxidant enzymes in Spodoptera littoralis (Boisduval): are they enhanced to protect gut tissues during oxidative stress? - Krishnan, Natraj; Kodrík, Dalibor (Journal of insect physiology, 2006)
The Egyptian armyworm Spodoptera littoralis is a polyphagous insect attacking a number of plant species including those belonging to the Solanaceae and Cruciferaceae families. Its digestive physiology must therefore adapt to the food plant to ensure maximum extraction of nutrients with minimum trade-off in terms of growth retardation by pro-oxidant allelochemicals. To investigate this, the caterpillars of S. littoralis were fed on a semi-artificial diet (Manduca Premix-Heliothis Premix) and for 24 h on potato plants (Solanum tuberosum), respectively, at the mature 6th instar, and the levels of oxidative radicals and antioxidant enzymes in their guts were compared. The gut pH, standard redox potential (Eh) and electron availability (pe) revealed that oxidizing conditions prevail which promote oxidation of pro-oxidant allelochemicals in foliage. Oxidative stress in the foregut and midgut tissue and the gut contents was assessed from the generation of superoxide radical, total peroxide content and protein carbonyl content. Antioxidant defense was measured by the activities of superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APOX) and glutathione S-transferase peroxidase (GSTpx). A significant (p < 0.001) increase in the superoxide radical production (in foregut tissue, foregut and midgut contents), concomitant with an increase in total peroxide (in foregut contents) and protein carbonyl levels (in foregut and midgut tissue) were noted in larvae fed on the plants in contrast to those fed the semi-artificial diet. Similarly, a significant up-regulation of antioxidant enzymes SOD (in midgut tissues), CAT (in foregut, midgut tissue and contents), APOX (in foregut contents, midgut tissue and contents) and GSTpx (in foregut tissues) was recorded on the plant diet in comparison to the semi-artificial diet. The pro-oxidant allelochemicals in the plant diet are thus eliminated by the insect at the expense of up-regulation of antioxidative enzymes in response to increased oxidative stress from oxidizable allelochemicals. The results are consistent with the hypothesis that increased concentrations of antioxidants form an important component of the defense of herbivorous insects against both exogenous and endogenous oxidative radicals.
Keywords: koncentrace vodíkových iontů; superoxidy; Hydrogen-Ion Concentration; Larva; Oxidative Stress; Superoxides; antioxidancia; gastrointestinální trakt; Gastrointestinal Tract; larva; zvířata; oxidační stres; Spodoptera; Antioxidants; Animals